Microscopic qualitative evaluation of fixation time and decalcification media in rat maxillary periodontium Avaliação microscópica qualitativa do tempo de fixação e dos meios de descalcificação do periodonto de ratos - Marilene Issa Fernandes; Eduardo José Gaio; Cassiano Kuchenbecker Rosing; Rui Vicente Oppermann; Pantelis Varvaki Rado (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The rat model is widely used in periodontal research and the quality of histological sections is essential. The purpose of this study was to evaluate the histological characteristics of periodontal tissues in Wistar rat maxillae, with different times of fixation and decalcified by nitric acid or formic acid (Anna Morse Solution). Fifteen rats were used. Fixation was performed for 24, 48 and 72 hours. The maxillae were hemi-sectioned and each part was decalcified either in nitric acid for 7 days or in Anna Morse solution for 35 days. Two trained and blinded examiners performed the evaluation. Fourty eight hours of fixation and decalcification with Anna Morse solution showed more clear characteristics of the epithelium-connective tissue interface and of the periodontal structures. Mean measurements between the cementum-enamel junction and the bone crest varied in the different experimental times from 176.5 (± 60.45) to 210.94 (± 39.33) pixels on the buccal aspect, and from 199.69 (± 38.33) to 298.55 (± 70.81) pixels on the palatal aspect, with no statistically significant differences (ANOVA, p > 0.05). In the same fixation period, decalcification with nitric acid or Anna Morse solution did not display any statistically significant differences. It may be concluded that for a qualitative histological analysis, fixation should preferably be for 48 hours and the demineralization should be made by Anna Morse solution. For a histomorphometric analysis, the decalcification solution does not interfere in the results. O modelo rato é extensamente usado na pesquisa periodontal, e a qualidade dos cortes histológicos é essencial. A proposta deste estudo foi avaliar as características histológicas dos tecidos periodontais nas maxilas de ratos Wistar, após diferentes períodos de fixação e descalcificação pelo ácido nítrico ou pelo ácido fórmico (Solução de Anna Morse). Quinze ratos foram usados. A fixação foi realizada nos períodos de 24, 48 e 72 horas. As maxilas foram divididas e parte foi descalcificada em ácido nítrico durante 7 dias e parte com solução de Anna Morse por 35 dias. Dois examinadores treinados e cegos executaram a avaliação. Quarenta e oito horas de fixação e descalcificação com solução de Anna Morse mostraram características mais evidentes da interface epitélio-conjuntivo, assim como das estruturas periodontais. As médias, por vestibular, entre a junção cemento-esmalte e a crista óssea nos diferentes tempos experimentais variaram entre 176,5 (± 60,45) e 210,94 (± 39,33) "pixels", e, na face palatina, entre 199,69 (± 38,33) e 298,55 (± 70,81) "pixels", sem nenhuma diferença estatisticamente significativa (ANOVA, p > 0,05). No mesmo período de fixação, a descalcificação com ácido nítrico ou solução de Anna Morse não mostrou diferenças estatisticamente significantes. Pode-se concluir que, para a análise histológica qualitativa, a fixação deve ser preferivelmente em 48 horas e a desmineralização por solução de Anna Morse. Para a análise histo-morfométrica, a solução descalcificadora não interferiu nos resultados.